2014
DOI: 10.1111/gbi.12095
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic oxidation of methane by sulfate in hypersaline groundwater of the Dead Sea aquifer

Abstract: Geochemical and microbial evidence points to anaerobic oxidation of methane (AOM) likely coupled with bacterial sulfate reduction in the hypersaline groundwater of the Dead Sea (DS) alluvial aquifer. Groundwater was sampled from nine boreholes drilled along the Arugot alluvial fan next to the DS. The groundwater samples were highly saline (up to 6300 mm chlorine), anoxic, and contained methane. A mass balance calculation demonstrates that the very low δ13CDIC in this groundwater is due to anaerobic methane oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 108 publications
(179 reference statements)
3
31
0
Order By: Relevance
“…Previous studies reported that sulfur-cycling AOM can induce sulfur isotope fractionation in marine environments and at sulfate concentrations in the millimolar range Antler et al, 2014Antler et al, , 2015Avrahamov et al, 2014;Deusner et al, 2014;Sivan et al, 2014). A few of these studies assigned ε AOM values of 20-30 for AOM in gas seeps (Deusner et al, 2014;Sivan et al, 2014) and suggested that AOM may cause fractionations of up to 60 in marine SMTZs Deusner et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported that sulfur-cycling AOM can induce sulfur isotope fractionation in marine environments and at sulfate concentrations in the millimolar range Antler et al, 2014Antler et al, , 2015Avrahamov et al, 2014;Deusner et al, 2014;Sivan et al, 2014). A few of these studies assigned ε AOM values of 20-30 for AOM in gas seeps (Deusner et al, 2014;Sivan et al, 2014) and suggested that AOM may cause fractionations of up to 60 in marine SMTZs Deusner et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that sulfurcycling AOM impacts not only sulfur (δ 34 S SO4 ), but also oxygen isotopes (δ 18 O SO4 ) in the dissolved sulfate pool and apparently creates an unique pattern among them that can help to distinguish between organotrophic and methanotrophic SR to be the main drivers of the footprints (e.g., Antler et al, 2014Antler et al, , 2015Avrahamov et al, 2014;Deusner et al, 2014). Therefore, future studies may probably be best approached by combined investigations of oxygen and sulfur isotopes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies have measured both the sulfur and oxygen isotope fractionation during sulfate-driven AOM, predominantly in the environment (12,55,56,70,71). The overall sulfur isotope fractionation during AOM in seeps has been shown to be lower than the sulfur isotope fractionation of traditional organoclastic bacterial sulfate reduction or sulfate-driven AOM in long, diffusive profiles.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the high salinity in the modern Dead Sea, evidence for microbial sulfate reduction, likely coupled to anaerobic methane oxidation, has been found in ground water and sedimentary deposits (Oldenburg et al, 2000a,b;Gavrieli et al, 2001;Avrahamov et al, 2014;Thomas et al, 2016). Microbial sulfate reduction has been inferred from the coexistence of aqueous sulfate and sulfide, as well as measurements of sulfur isotopes that suggest a sulfur isotope fractionation of about 30 in the modern Dead Sea (Gavrieli et al, 2001).…”
Section: Introduction Overviewmentioning
confidence: 99%